Islam, violence et démocratie au Proche-Orient. Les islamistes palestiniens face aux défis de l'accord « Gaza-Jéricho » - Tlemçani, Rachid (Études internationales, 1994)
On September 13, 1993, the Jewish state signed a peace agreement with the PLO dealing with the Gaza Strip and Jericho. This historic agreement quickly raised hopes throughout the world because it brought an end to relations of hostility between two peoples coveting the same land. On the ground, however, due to the intransigence of the israeli government, the situation has rapidly deteriorated between Muslim fundamentalists and Jewish settlers. The Islamic fundamentalist movement is attempting to hinder implementation of the Oslo agreement by acts of violence. A year after the signing of the Oslo agreement, it is worthwhile to begin with an overview of Palestinian Islamic fundamentalist groups and the many challenges of the "Gaza-Jericho" agreement. Such a study, in opposition to a simplistic view, does not allow us to perceive the Islamic fundamentalist movement as being a single homogeneous entity with a ready-made ideology and well-defined courses of action. The largest Islamic movement, Hamas, is willing, for example, to the part in the future election in contrast to the discourse it has held up to the present time. Hamas' opposition to the peace plan ultimately comes down to a struggle for control over the institutions of the future "Palestinian State". In the final analysis, the split between Fatah and Hamas, and between democrats and Islamic fundamentalists in Arab countries, reflects two populist variants arising from an authoritarian system.